2021
DOI: 10.1111/jfbc.13665
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of Chlorella pyrenoidosa drink on healthy subjects: A randomized, placebo‐controlled, double‐blind, cross‐over clinical trial

Abstract: The current study aims to explore the anti-inflammatory activity of Chlorella pyrenoidosa on RAW 267.4 cells and followed by a cross-over clinical trial in healthy subjects to check the antioxidant and anti-aging properties of Chlorella water extract (CWE).For the clinical trial, 44 healthy subjects were requested to consume 27 ml of either placebo or CWE for 90 days (phase I) and vice-versa manner for 90 days (phase II) with 4 weeks of washout period. The RAW 264.7 macrophages treated with Chlorella display p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…To date, trials on humans are available for a few microalgae and are often based on dietary treatments for a few weeks. In this regard, some relevant findings are available for Phaeodactylum tricornutum (Bacillariophyta) [256], species of the genus Chlorella (Trebouxiophyceae) [257][258][259][260][261][262], Haematococcus pluvialis (Chlorophyceae) [263][264][265][266], species of the genus Tetraselmis (Chlorodendrophyceae) [267], Euglena gracilis (Euglenophyceae) [268], species of the genus Nannochloropsis (Eustigmatophyceae) [269] and cyanobacteria of the genus Arthrospira (Cyanophyceae) [270,271].…”
Section: Figurementioning
confidence: 99%
“…To date, trials on humans are available for a few microalgae and are often based on dietary treatments for a few weeks. In this regard, some relevant findings are available for Phaeodactylum tricornutum (Bacillariophyta) [256], species of the genus Chlorella (Trebouxiophyceae) [257][258][259][260][261][262], Haematococcus pluvialis (Chlorophyceae) [263][264][265][266], species of the genus Tetraselmis (Chlorodendrophyceae) [267], Euglena gracilis (Euglenophyceae) [268], species of the genus Nannochloropsis (Eustigmatophyceae) [269] and cyanobacteria of the genus Arthrospira (Cyanophyceae) [270,271].…”
Section: Figurementioning
confidence: 99%
“…Several investigations have evaluated the effects of microalgae ingestion on DHEA. Chiu et al (2021), in a double-blind randomized clinical trial, observed increases in DHEA related to the intake of a Chlorella pyrenoidosa extract beverage in 44 healthy participants [44]. To the best of our knowledge, this is the only study evaluating the possible effects of a microalga on this hormone in a human organism.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, the Chlorella pyrenoidosa water extract showed anti-aging effects of Chlorella pyrenoidosa especially in the healthy individuals. The impacts were mediated by significantly downregulated inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2), and improved antioxidant levels (SOD, CAT TEAC, and DHEAs) and suppressed oxidative stress/aging markers (TBARS and 8-OHdG) in addition to protecting liver (reduced oxaloacetic transaminase and serum glutamic pyruvic transaminase) [ 68 ]. As per a clinical report, the daily consumption of chlorella can remarkably inhibit total cholesterol, very low-density lipoprotein cholesterol, apolipoprotein B, triglycerides, in mild hypercholesterolemic adults [ 69 ].…”
Section: Discussionmentioning
confidence: 99%